2021
DOI: 10.1002/app.51401
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and mechanical properties of partially bio‐based PP/PBS blends nanocomposites elaborated by twin‐screw extrusion

Abstract: Organically modified montmorillonite (OMMT, Cloisite 20) was used as reinforcing filler to prepare nanocomposites from a blend of polypropylene (PP) and eco-friendly degradable polybutylene succinate (PBS). A PP grafted with maleic anhydride was also added as a compatibilizer. Scanning electron microscopy observations indicated that the blend morphology was affected by the presence of OMMT, which acted as a compatibilizer between PP and PBS.Rheological measurements showed a significant increase of the complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Figure 9A shows that the viscosities of the blends and composites decrease with increasing shear rates, indicating shear thinning and non‐Newtonian behaviors. Previous works have clearly suggested that there are large differences in the viscosities between neat PP and PBS, with the viscosity of PP being more than 1000 times that of neat PBS 28 . Hence, the non‐compatibilized blend (50PP/PBS) has the lowest viscosity and shows no dependence on changes in the angular frequency.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Figure 9A shows that the viscosities of the blends and composites decrease with increasing shear rates, indicating shear thinning and non‐Newtonian behaviors. Previous works have clearly suggested that there are large differences in the viscosities between neat PP and PBS, with the viscosity of PP being more than 1000 times that of neat PBS 28 . Hence, the non‐compatibilized blend (50PP/PBS) has the lowest viscosity and shows no dependence on changes in the angular frequency.…”
Section: Resultsmentioning
confidence: 96%
“…It is also reported that the peaks at 2 θ = 14.1°, 16.8°, 18.5° are related to the (110), (040), and (130) crystal planes of the α‐phase crystal of PP while there is a small peak attributed to the (300) crystal plane of β‐phase crystal plane of PP at 16.1°. On the other hand, PBS has α‐phase monoclinic crystals represented by crystal planes (020), (021), (110), and (111) at 2 θ = 19.6°, 21.9°, 22.6°, and 28.7° 28,44 . The results indicated that the position of XRD peaks of each polymer did not change, regardless of the PP loading content or addition of compatibilizer.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations